Предмет: Алгебра,
автор: Kud88
(x-2)^2=(x+3)^2 решите уравнение
Ответы
Автор ответа:
0
По формуле a^2 - b^2 = (a - b)* (a + b)
(x-2)^2 - (x+3)^2 = 0
(x - 2 - (x + 3)) * (x - 2 + x + 3) = 0
(x- 2 - x - 3) * ( x - 2 + x + 3)= 0
- 6* (2x + 1) = 0
2x = - 1
x = - 1/2 = - 0 .5
(x-2)^2 - (x+3)^2 = 0
(x - 2 - (x + 3)) * (x - 2 + x + 3) = 0
(x- 2 - x - 3) * ( x - 2 + x + 3)= 0
- 6* (2x + 1) = 0
2x = - 1
x = - 1/2 = - 0 .5
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Русский язык,
автор: aydanadocha2009
Предмет: История,
автор: midinakabaeva48
Предмет: Математика,
автор: SnowLeopard2001